Determining the capabilities of artificial intelligence on the development of cryptotrading and blockchain technology - Andriushchenko, Kateryna; Riepina, Inna; Buriachenko, Andrii; Kyryliuk, Oksana (Technology audit and production reserves, 2025)
The object of research is crypto trading and blockchain technologies, including the development of trading bots and the implementation of automated risk management systems. AI includes the development of trading bots, the implementation of automated risk management systems, and the use of predictive analytics tools that optimize trading operations. This is important, as AI technology plays a crucial role in the rapid analysis of huge amounts of data to predict market prices and trading opportunities, thereby increasing the efficiency of investments. In addition, AI provides investors with real-time information and assists in risk management. However, there are objective difficulties, and crypto fraudsters study different scenarios and adapt to changing market conditions using AI. By using the methods of observation, generalization, systematization and comparison, the authors have achieved results in determining the significance of implementation. In particular, the integration of artificial intelligence and cryptocurrencies can be applied, which aims to use the capabilities of big data processing and continuous learning to create a more efficient trading environment and financial services. The results presented in this paper give grounds to assert that it is possible to implement in the real business and technological environment (exchanges, crypto-exchanges, cryptocurrency operations, IT infrastructure, big data, AI). The article proposes innovative models and applications of artificial intelligence for use in trading business operations, where the main tool for users is generative artificial intelligence and interfaces. This method makes it possible to define generative artificial intelligence and natural language interfaces as the main means for trading operations that will be carried out using cryptocurrencies. As a result, real-time cryptocurrency trading and investment strategies based on data and algorithms have become possible.